CREATING AN IQ DEVELOPMENT MOBILE APPLICATION FOR SCHOOL CHILDREN - Kayumov Ahror; Janayev Izzatillo (Web of Journals Publishing, 2024)
This study aims to explore fourth-grade students' perceptions of mobile programming education. Data from interviews, metaphors, and drawings were gathered and analyzed qualitatively. Among 135 participants, 24 fourth-graders were purposefully selected. Results indicate positive impacts on students' skills and recommend MIT App Inventor for programming education.
Keywords: Primary school students, mobile programming education, fourth-grade, views, qualitative research, interviews, metaphor, drawings, purposeful sampling, content analysis, MIT App Inventor, skills, creative thinking, social skills.